MathsGee is Zero-Rated (You do not need data to access) on: Telkom |Dimension Data | Rain | MWEB

0 like 0 dislike
98 views
Determine $f'(x)$ from first principles if: $f(x) = x^{2} -6x$
| 98 views

0 like 0 dislike
h is the small change

dy/dx = [(x+h)^2 - 6(x+h) - (x^2 -6)]/h

= (x^2 + 2xh +h^2 -6x-6h-x^2 +6)/h

= (2xh+h^2 -6h)/h

= h(2x + h -6)/h

= 2x+h-6   , as h is a very small change

= 2x + 0 -6

= 2x-6
by Diamond (45,616 points)

0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
1 like 0 dislike
1 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
1 like 0 dislike
0 like 0 dislike
1 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
1 like 0 dislike
0 like 0 dislike
0 like 0 dislike
3 like 0 dislike
1 like 0 dislike
0 like 0 dislike
0 like 0 dislike
2 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike